Smart-Working: Work Flexibility without Constraints - Marta Angelici; Paola Profeta (Center for Economic Studies and ifo Institute (CESifo), 2020)
Does removing the constraints of time and place of work increase the utility of workers and firms? We design a randomized experiment on a sample of workers in a large Italian company: workers are randomly divided into a treated group that engages in flexible space and time job (which we call "smart-working") one day per week for 9 months and a control group that continues to work traditionally. By comparing the treated and control workers, we find causal evidence that the flexibility of smart-working increases the productivity of workers and improves their well-being and work-life balance. We also observe that the effects are stronger for women and that there are no significant spillover effects within workers of a team.
Keywords: J16; J22; J24; L20; M54; 330; randomized control trial; productivity; work-life balance; well-being